THE CONTRIBUTION OF MASTERY OF THEORY TO CORPSE MANAGEMENT SKILLS AT KULLIYYATUL MUBALLIGHAAT AL-ISLAMIYYAH AL-ISHLAH BONDOWOSO 2021/2022 ACADEMIC YEAR - Agusyanto; Nur Amina Laan (Tsaqofah : Jurnal Pendidikan Islam, 2024)
This study aims to determine whether there is a relationship between mastery of theory and skills in funeral management at Kulliyyatul Muballighaat Al-Islamiyyah Al-Ishlah Bondowoso in the 2021/2022 academic year. this study aims to obtain information about whether there is a positive relationship between mastery of the theory of funeral management and students' skills in funeral management. This research was conducted at the Muadalah educational institution (equivalent to junior or senior high school) at Kulliyyatul Muballighaat Al-Islamiyyah Al-Ishlah Bondowoso. The data collection time was held on June 12, 2021 to July 10, 2021. Based on the results of statistical analysis, the data that has been obtained are; the average score for mastery of the theory of corpse management is 26.71 and the average score for corpse management skills is 112.36. Thus it can be said that the mastery of the theory of corpse management and corpse management skills is very satisfying.